Insurance companies and the growth of corporate loans' securitization - Fulvia Fringuellotti; Jo\~ao A. C. Santos (Federal Reserve Bank of New York, 2021)
We show that insurance companies have almost nonupled their investments in collateralized loan obligations (CLOs) in the post-crisis period, reaching total holdings of 125 billion in 2019. The growth in CLOs' investments has far outpaced that of loans and corporate bonds, and was characterized by a strong preference for mezzanine tranches rated investment grade over triple-A rated tranches. We document that these phenomena reflect a search for yield behavior. Conditional on capital charges, insurance companies invest more heavily in bonds and CLO tranches with higher yields. Preferences for CLO tranches derived from tranches' higher yields relative to bonds with the same rating, and increased following the 2010 capital regulatory reform, resulting in insurance companies holding more than 40 percent of mezzanine tranches outstanding in 2019. In the process, insurance companies created the demand for the risky tranches that are critical to the CLO issuance.
Keywords: G11; G20; G22; 330; insurance companies; CLOs; regulatory arbitrage; corporate loans; securitization